الأصول اللاملموسة مصدر جوهري للميزة التنافسية في ظل اقتصاد المعرفة - بومجان, عادل; قريشي, محمد (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2019)
إن المتتبع لمختلف مراحل تطور النشاط الاقتصادي، يلمس تغيرات كبيرة مست أوجه النشاطات الاقتصادية ، سيما منذ نهاية الثمانينات وبداية التسعينات، هذه التحولات تعلقت أساسا ببروز وبزوغ حقبة ومرحلة اقتصادية جديدة تجلت فيه العديد من المظاهر والخصائص والآثار التي اختلفت بصورة كبيرة عن المراحل التي سبقتها والتي سميت باقتصاد المعرفة أو الاقتصاد الرقمي أو المبني على المعرفة.    أصبحت المعرفة المورد الأساس المحرك للإنتاج والنمو للاقتصاديات والمجتمعات، وأصبحت تشكل الركيزة الأساسية في خلق القيمة وأنها المصدر الجوهري للمزايا التنافسية واستدامتها، والمرتبطة ارتباطا وثيقا بالقدرات التي تمتلكها المؤسسة، وكذا رأسمالها الفكري أو ما يسمى بالأصول اللاملموسة، يهدف هذا المقال الى ابراز خصائص الموارد التنافسية باسقاط مختلف مقارباتها على الاصول اللاملموسة والتميز لرأسمالها الفكري. الكلمات المفتاحية :المعرفة،اقتصاد المعرفة، الميزة التنافسية،رأس المال الفكري،الأصول اللاملموسة.     Abstract    The trajectory of the various stages of the development of economic activity has been marked by significant changes in economic activities, especially since the end of the 1980s and the beginning of the 1990s. These changes were mainly related to the emergence and emergence of a new era and economic stage, which revealed many aspects, characteristics and effects that differed considerably from the previous stages, In the knowledge economy or the digital or knowledge-based economy.  knowledge has become the basis for the production and economic growth of the Satiate communities and become a fundamental pillar in the creation of value and it is the fundamental source of competitive advantages and sustainability, and is closely linked to the capabilities possessed by the institution, as well as the intellectual capital or the so-called intangible assets, This article aims to highlight the characteristics of competitive resources by dropping their various approaches to the intangible assets and the excellence of their intellectual capital. Keywords: knowledge, knowledge economy, competitive advantage, intangible assets.